EVALUATION OF QUALITY ASSURANCE OF PRIMARY SCHOOL EDUCATION IN PONOROGO REGENCY - Tri Budhi Susilowati; V. Rudi Handoko; Bambang Kusbandrijo (DIA: Jurnal Administrasi Publik, 2023)
Quality assurance of national education is carried out to educate the nation's life and shape the character and civilization of a dignified nation through the SNP. The principle is to encourage managers, administrators, and education units to improve their performance in providing quality educational services and software to encourage transparency and public accountability. In its implementation, education quality assurance policies must adapt to changes and developments in science and technology and rapid global dynamics. The quality of Indonesian education has not been as expected. Accreditation to BAN-S/M, the development of school quality has not shown an encouraging development in the quality of education. The factor is not that the SNP is of low quality but that the fulfillment and implementation of the SNP have not been running optimally. The objective of this research is to: 1) Describe and analyze the evaluation of quality assurance policies for primary school education in Ponorogo; 2) Examine the factors that encourage and obstruct education quality assurance.; 3) look at the quality and functional education quality assurance model. This research uses a qualitative descriptive research method. The data analysis technique used was evaluation. Data were analyzed interactively.